Power Loss and Thermal Analysis of a MW High-Speed Permanent Magnet Synchronous Machine - Yue Zhang; McLoone, Sean; Wenping Cao; Fengyi Qiu; Gerada, Chris (IEEE transactions on energy conversion, 2017)
High-speed permanent magnet synchronous machines (PMSMs) have attracted much attention due to their high power density, high efficiency, and compact size for direct-drive applications. However, the consequent power loss density is high, and hence heat dissipation is a major technical challenge. This is particularly the case for high-speed operation. In this paper, a MW level high-speed PMSM is designed and its electromagnetic and mechanical power losses comprehensively investigated using finite element analysis. The transient machine demagnetization performance is studied, and a composite rotor structure is proposed to improve machine antidemagnetization capability. The temperature distribution of the proposed high-speed PMSM is also analyzed using a fluid-thermal coupling method with calculated power loss. Experiments conducted on a prototype of the high-speed PMSM demonstrate the effectiveness of the numerical models developed and validate the results obtained.